Wave Propagation Concepts for Near-Future Telecommunication Systems - Costanzo, Sandra (IntechOpen, 2017)
Wave Propagation Concepts for Near-Future Telecommunication Systems is an edited book discussing recent researches for the development of innovative telecommunication systems, with particular focus on the propagation aspects and radiating systems design. It is divided into two sections: Section 1, devoted to the illustration of advanced results in terms of microwave propagation at high operating frequencies, and Section 2, illustrating new electromagnetic concepts and applications.